1996
DOI: 10.1111/j.1398-9995.1996.tb04683.x
|View full text |Cite
|
Sign up to set email alerts
|

Indoor mite allergens in patients with respiratory allergy living in Porto, Portugal

Abstract: We investigated the levels of mite allergens (Der p 1, Der f 1, Der 2, and Lep d 1) in dust samples from the homes of 59 patients with asthma, 36 sensitized to house‐dust mites (HDM) and 23 to grass pollen (controls), living in Porto, northern Portugal. The relationship between exposure and sensitization to HDM and the influence of housing conditions on mite‐allergen levels were also evaluated. Der p 1 (median 9.2 μg/g) and Der 2 (4.6 μg/g) were the main allergens, while Der f 1 and Lep d 1 levels were always … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…A relationship between exposure and sensitization to Der p 1 has been shown in many other investigations (25,26,34) and was con®rmed in a multiple logistic regression model in our study. Because of the high Der p 1 and Der 2 levels in farmers' beds, it might have been expected that these farmers would have a higher sensitization rate than the urban population; however, the prevalence of sensitization to house-dust mites among the farmers was not signi®cantly higher than that of a randomly selected urban population (35) in the same region of Germany (farmers vs urban dwellers aged 20±44: 24% vs 19%).…”
Section: Discussionsupporting
confidence: 83%
“…A relationship between exposure and sensitization to Der p 1 has been shown in many other investigations (25,26,34) and was con®rmed in a multiple logistic regression model in our study. Because of the high Der p 1 and Der 2 levels in farmers' beds, it might have been expected that these farmers would have a higher sensitization rate than the urban population; however, the prevalence of sensitization to house-dust mites among the farmers was not signi®cantly higher than that of a randomly selected urban population (35) in the same region of Germany (farmers vs urban dwellers aged 20±44: 24% vs 19%).…”
Section: Discussionsupporting
confidence: 83%
“…There are 16 published studies from around the world which have examined the relationship between mite allergen levels and housing characteristics [8, 9, 15–28], some of which were too small to perform multivariate analyses [18–21, 27] and some studied homes of asthma patients only [18–21, 23]. Although housing designs and climates are very different in different parts of the world, some common themes have emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Four of the five studies in which age of the carpet was measured found older carpets to contain higher mite allergen levels in a multivariate analysis [8, 16, 24, 25], similarly for five of the seven studies in which the age of the mattress was measured [8, 9, 16, 17, 25]. Of the 12 studies in which the presence of damp was recorded, five studies found it to be associated with higher levels in a multivariate analysis [9, 17, 22, 25, 26], and four found an association in the univariate analysis [16, 19–21]. The association between older homes and higher levels of mite allergen was not clear, although different studies used different age bandings for the homes.…”
Section: Discussionmentioning
confidence: 99%
“…There is no commercial method available for measuring storage mite allergens. The allergens from the storage mite L. destructor such as Lep d1 and Lep d2 have been purified and characterised and a method for measuring allergens in dust samples has been developed [26][27][28][29][30]. We need new commercial methods for measuring storage mite allergens in order to comprehensively study the possible role of mites in sensitising people in moisture damaged buildings.…”
Section: Discussionmentioning
confidence: 99%